The Nobility of Mughal Emperors: A Comprehensive Analysis - Dhruv Dev Chauhan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research paper aims to explore the nobility of the Mughal Emperors who ruled over the Indian subcontinent from the early 16th century to the mid-19th century. The paper will delve into the various aspects of nobility, including their lineage, character, governance, cultural patronage, and military prowess. It will also examine the impact of the Mughal Emperors on the society and economy of the time. Through a thorough analysis of the primary and secondary sources, the research paper will present a detailed account of the nobility of each Mughal Emperor, highlighting their achievements and contributions to the empire. Additionally, the paper will discuss the challenges faced by the Mughal Emperors and how they navigated them with their nobility intact.